Variations in Well-Being as a Function of Paranormal Belief and Psychopathological Symptoms: A Latent Profile Analysis - Dagnall, Neil; Denovan, Andrew; Drinkwater, Kenneth Graham (Frontiers in Psychology, 2022)
This study examined variations in well-being as a function of the interaction between paranormal belief and psychopathology-related constructs. A United Kingdom-based, general sample of 4,402 respondents completed self-report measures assessing paranormal belief, psychopathology (schizotypy, depression, manic experience, and depressive experience), and well-being (perceived stress, somatic complaints, and life satisfaction). Latent profile analysis identified four distinct sub-groups: Profile 1, high Paranormal Belief and Psychopathology (n = 688); Profile 2, high Paranormal Belief and Unusual Experiences; moderate Psychopathology (n = 800); Profile 3, moderate Paranormal Belief and Psychopathology (n = 846); and Profile 4, low Paranormal Belief and Psychopathology (n = 2070). Multivariate analysis of variance (MANOVA) found that sub-groups with higher psychopathology scores (Profiles 1 and 3) reported lower well-being. Higher Paranormal Belief, however, was not necessarily associated with lower psychological adjustment and reduced well-being (Profile 2). These outcomes indicated that belief in the paranormal is not necessarily non-adaptive, and that further research is required to identify the conditions under which belief in the paranormal is maladaptive.